Finite-difference and pseudo-spectral methodsfor the numerical simulations of in vitro human tumor cellpopulation kinetics - Z. Jackiewicz; B. Zubik-Kowal; B. Basse (Mathematical Biosciences and Engineering)
Pseudo-spectral approximations areconstructed for the model equations describing the populationkinetics of human tumor cells in vitro and their responses toradiotherapy or chemotherapy. These approximations are moreefficient than finite-difference approximations. The spectralaccuracy of the pseudo-spectral method allows us to resolve themodel with a much smaller number of spatial grid-points thanrequired for the finite-difference method to achieve comparableaccuracy. This is demonstrated by numerical experiments which show agood agreement between predicted and experimental data.